Knowledge, Attitude, and Practices Among the General Population During the Later Stage of the COVID-19 Pandemic in Malaysia: A Cross-Sectional Study - Chai, Chee Shee; Ng, Diana Leh Ching; Chua, Wei Jing; Tung, Yu Zhen; Woweham, Sindeh; Muhammad Amin, Ibrahim; Siti Fatimah, Badlishah Sham; Tan, Seng Beng (Dovepress, 2022)
Purpose: A different pattern of mental health issues was reported during the later stage of the COVID-19 pandemic; however, few studies have examined Malaysians’ knowledge, attitudes, and practices (KAP) prevalent during this time. Patients and Methods: A nationwide online cross-sectional study was conducted in Malaysia from June 1, 2021 to June 14, 2021, ie, 18-months from the first reported COVID-19 case in the country. Citizens aged 18 years and above were recruited by means of the snowball sampling method. ANOVA, Pearson correlation, and linear regression tests were used. Results: Of the 2168 respondents, most were young adults (62.7%), females (62.4%), tertiary educated individuals (84%), non-health care workers (85.9%), and individuals who knew someone diagnosed with COVID-19 (75.2%). The mean score for knowledge was 10.0 ± 1.52 (maximum score = 12); correct response rate for each question ranged from 54.2% to 99%. The mean score in terms of attitude was 1.3 ± 0.85 (maximum score = 2); 68.7% respondents agreed that control over COVID-19 would finally be achieved; and 62.3% believed that Malaysia could conquer COVID-19. The mean score for practices was 5.1 ± 1.10 (maximum score = 6); 81.5%, 88.1%, and 74.1% respondents avoided crowded places, confined spaces, and conversations in close physical proximity, respectively. Furthermore, 94.2% wore masks when leaving home; 89.0% practiced hand hygiene; and 83.8% adhering to COVID-19 warnings. Small but significant correlations were found between knowledge and attitude (r = 0.078, p < 0.001) as well as between knowledge and practices (r = 0.070, p = 0.001). Conclusion: Malaysians exhibited sound knowledge but negative attitudes and inadequate practices pertaining to COVID-19 during the pandemic’s later stage. At this phase, unlike at the early stage, the public’s sound knowledge ensured little improvement in their attitudes and practices. Therefore, health education at the later pandemic stage should focus on promoting positive attitudes and developing better practices.